2016
DOI: 10.1080/00028487.2016.1209556
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Genetic Structure and Site Fidelity among Native Muskellunge Populations in Lake Huron and Georgian Bay

Abstract: Conservation and management issues related to genetic diversity and stock structure of native populations of Muskellunge Esox masquinongy have largely been unexplored. In Lake Huron's North Channel and Georgian Bay, Muskellunge populations have been impacted by historical commercial fisheries, recreational fisheries, loss of spawning habitat, historical water quality issues, and ecosystem changes. To determine the spatial genetic structure of native Muskellunge in Lake Huron and Georgian Bay, spawning adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
13
11
0
Order By: Relevance
“…We observed levels of variation similar to other studies (Wilson et al. ) and significant population differentiation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We observed levels of variation similar to other studies (Wilson et al. ) and significant population differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…This is slightly lower but similar to the number of alleles observed in Lake Huron Muskellunge (truenormalXfalse¯ = 9.6 alleles per locus; Wilson et al. ). After adjusting for multiple comparisons (adjusted P = 0.001), 4 of 55 comparisons identified significant departures from Hardy–Weinberg equilibrium ( EmaD5 and EmaD6 in locality 4, Buckhannon River, and locality 6, Middle Island Creek).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In conclusion, understanding population structure of species residing in connected habitats and in sympatry at certain times of the year and/or life cycle has proved critical for maintaining sustainable fisheries (Hilborn et al, 2003;Brenden et al, 2015;Wilson et al, 2016). Here, we showed that yellow perch from Lake Michigan and DRMs represent distinct stocks and that Lake Michigan yellow perch can reside in DRMs during autumn, where they may be subjected to greater harvest than in Lake Michigan.…”
Section: Discussionmentioning
confidence: 71%